Development of Nutrient Rich Value-added Biscuit through Incorporation of Orange-fleshed Sweetpotato Puree - Hossain, M.M.; Heck, S.; Chanda, D.; Rahaman, E.H.M.S.; Mahmood, S.; Kabir, M.H. (AI Publications, 2022)
Abstract— In Bangladesh bakery and confectionery industry has become almost self-sufficient in meeting the local demand. But the products produce from the factories cannot fulfill nutritional demand of the people of Bangladesh as wheat flour is the main ingredient of the bakery products. Orange Fleshed Sweetpotato is a promising root crop due to high beta carotene content and other vitamins and minerals could be used to reduce the gap of nutritional demand. The experiment was conducted with four BARI (Bangladesh Agricultural Research Institute) released orange fleshed sweetpotato varieties and a local cultivar at the GUK’s ‘Super Tasty Food’ Products Factory, Nashratpur, Gaibandha, Bangladesh during 2020-21 cropping season. The aim of the study was to develop nutrient rich valueadded biscuit for the consumers. Eleven treatments (formulations) were used to develop biscuit. The highest amount of beta carotene content was recorded in T4 treatment (1.67 mg/100g) followed by T9 treatment (0.84 mg/100g) and the lowest was obtained from T11 treatment (0.01 mg/100g). Maximum amount of vitamin C detected in T5 treatment (1.81 mg/100g) which was statistically similar to T1 treatment (1.74 gm/100g) and no Vitamin C was found in T11 treatment. Zinc content found maximum in T11 treatment (2.04 mg/100g) while the lowest was observed in T5 treatment (1.12 mg/100g). The highest amount of iron was recorded in T3 treatment (6.52 mg/100g) which is significantly similar to treatment T2 (6.43 mg/100g) and T8 (6.09 mg/100g), respectively. The entire sensory attributes of valueadded biscuit were accepted as fair to very good and have no remarkable difference from traditional biscuits (T11). The overall acceptability of the biscuit was found to be highest in T9 treatment (good to very good).